Divide and school gender and class dynamics in comprehensive education - Abraham, John (Falmer Press, 1995)
To further the ideals of comprehensive education the author proposes that streaming should be minimized; subject option processes should be intervention and counter-hegemonic; breadth of gender identities amongst the pupil population needs to be better appreciated; teacher trainees should be allowed sufficient time to develop a good awareness of the gender and class divisions in society; anti-sexist pedagogies should be systematically developed. Abraham concludes, however, that recent government reforms in education are more likely to hinder than further these proposals
Keywords: Klassenverhoudingen; Middenschool; Scholengemeenschappen; Sekseverschillen; Voortgezet onderwijs; Geschlechtsunterschied; Gesellschaft; Education, Secondary -- Social aspects -- Great Britain -- Case studies; High school students -- Great Britain -- Social conditions -- Case studies; Sex differences in education -- Great Britain -- Case studies; Sex discrimination in education -- Great Britain -- Case studies; Soziale Klasse; Gesamtschule; Gesamtschüler; Großbritannien; Fallstudiensammlung